2016
DOI: 10.1007/s13300-016-0218-3
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of IDegLira (Insulin Degludec/Liraglutide Combination) in Adults with Type 2 Diabetes Inadequately Controlled with a GLP-1 Receptor Agonist and Oral Therapy: DUAL III Randomized Clinical Trial

Abstract: IntroductionThe progressive nature of type 2 diabetes necessitates treatment intensification. This often involves intensification with oral antidiabetic drugs (OADs) initially, followed by other agents, such as glucagon-like peptide-1 receptor agonists (GLP-1RAs), with the majority of patients eventually requiring insulin therapy. Therefore, this trial aimed to investigate the efficacy of IDegLira (combination of insulin degludec and liraglutide) in controlling glycemia in adults with type 2 diabetes who were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
152
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(167 citation statements)
references
References 25 publications
11
152
1
1
Order By: Relevance
“…In 26‐ (DUAL I) and 32‐week (DUAL VI) clinical trials involving patients uncontrolled on metformin ± pioglitazone, end‐of‐trial HbA1c ranged from 42 mmol/mol to 46 mmol/mol (6.0% to 6.4%) and was achieved at a mean dose of 38 to 41 U . Similar differences between real‐world data presented here and clinical trial data were observed for patients on basal insulin and GLP‐1RA . It is not clear why more stringent glycaemic targets were not pursued more aggressively, but reasons might relate to country‐specific guidelines, the expense/availability of further uptitration, patient‐led titration being guided by fear of hypoglycaemia, and other patient characteristics (e.g.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…In 26‐ (DUAL I) and 32‐week (DUAL VI) clinical trials involving patients uncontrolled on metformin ± pioglitazone, end‐of‐trial HbA1c ranged from 42 mmol/mol to 46 mmol/mol (6.0% to 6.4%) and was achieved at a mean dose of 38 to 41 U . Similar differences between real‐world data presented here and clinical trial data were observed for patients on basal insulin and GLP‐1RA . It is not clear why more stringent glycaemic targets were not pursued more aggressively, but reasons might relate to country‐specific guidelines, the expense/availability of further uptitration, patient‐led titration being guided by fear of hypoglycaemia, and other patient characteristics (e.g.…”
Section: Discussionsupporting
confidence: 58%
“…The efficacy and safety of IDegLira has been evaluated in patients with T2D and suboptimal glycaemic control on oral antidiabetic drugs (OADs), GLP‐1RA therapy and basal insulin therapy in the phase III DUAL clinical trial programme . DUAL I–VII demonstrated that IDegLira combined the clinical advantages of both mono‐components to reduce both fasting and prandial blood glucose levels and, furthermore, mitigated the major side effects associated with insulin (hypoglycaemia, weight gain) and GLP‐1RA therapy (nausea) …”
Section: Introductionmentioning
confidence: 99%
“…The FPG at baseline was 7.3/ 7.4 mmol/L in one trial [6], whereas baseline FPG values ranged from 8.9 to 9.9 mmol/L in the other two IGlarLixi trials [3,4] and all the IDegLira trials [2,5,[7][8][9]. Furthermore, the target FPG was 4.4-5.6 mmol/L in all the IGlarLixi trials, whereas it was 4.0-5.0 mmol/L in all but one of the IDegLira trials.…”
Section: Heterogeneity Of the Included Studiesmentioning
confidence: 93%
“…First, the baseline medication differed between trials so that, depending upon the trial, some patients were previously on oral antidiabetic drugs (OADs) [2][3][4], some on basal insulin and OADs [5,6], and some on maximum tolerated dose of a GLP-1 RA [7]. These differences have not been accounted for in the analysis and can profoundly affect the possible impact of the FRC and therefore the conclusions of the analysis.…”
Section: Heterogeneity Of the Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation